Effect of Lycium barbarum Polysaccharide on Decreasing Serum Amyloid A3 Expression through Inhibiting NF-κB Activation in a Mouse Model of Diabetic Nephropathy - Fengqi Wan; Fulin Ma; Jiaxin Wu; Xinyu Qiao; Minxue Chen; Wenjian Li; Liang Ma (Analytical Cellular Pathology)
Lycium barbarum polysaccharide (LBP) as one of the main bioactive constituents of the fruit of Lycium barbarum L. (LBL.) has many pharmacological activities, but its antihyperglycemic activity is not fully understood yet. This study investigated the hypoglycemic and renal protective effects of LBP on high-fat diet/streptozotocin- (HFD/STZ-) induced diabetic nephropathy (DN) in mice. Blood glucose was assessed before and after 8-week administration of LBP, and the homeostasis model assessment-insulin resistance (HOMA-IR) index was calculated for evaluating the antidiabetic effect of LBP. Additionally, serum creatinine (sCr), blood urea nitrogen (BUN), and urine microalbumin were tested to evaluate the renal function. HE and PAS stainings were performed to evaluate the morphology and injury of the kidney. The results showed that LBP significantly reduces the glucose level and ameliorates the insulin resistance of diabetic mice. Importantly, LBP improves renal function by lowering the levels of sCr, BUN, and microalbumin in diabetic mice and relieves the injury in the renal glomeruli and tubules of the DN mice. Furthermore, LBP attenuates renal inflammation as evidenced by downregulating the mRNA levels of TNFα, IL1 β, IL6, and SAA3 in the renal cortex, as well as reducing the elevated circulating level and protein depositions of SAA3 in the kidney. In addition, our western blot results showed that NF-κB p65 nuclear translocation and the degradation of inhibitory κB-α (IκBα) occurred during the progress of inflammation, and such activated signaling was restrained by LBP. In conclusion, our findings suggest that LBP is a potential antidiabetic agent, which ameliorates the inflammation in DN through inhibiting NF-κB activation.